Quantum interferometers as quantum computers - Ekert, A (1998)
Quantum computers which use quantum interference of different computational paths to enhance correct outcomes and suppress erroneous outcomes of computations can be viewed as multiparticle interferometers. I discuss this approach to quantum computation and argue that it provides additional insights into the nature of quantum algorithms.